No Time Like the Present: Nadine Gordimer and the Burden of Telos. Issue 2 (2nd April 2016) - Titlestad, Michael
Summary: Nadine Gordimer was widely criticised for her failure to take a stand against the injustices manifest in the post-apartheid regime (during the presidencies of Thabo Mbeki and Jacob Zuma). No Time Like the Present (2012) apparently set out to rectify this neglect: it presents a catalogue of contemporary failures, injustices and abominations, touching on almost every index of state failure. At the same time, the novel sanctifies both the struggle against apartheid and the brave comrades who fought for justice. Without challenging the rectitude of the anti-apartheid cause of activists, the article questions whether – in her final novel – Gordimer did not succumb to a version of "theology" that (in attributing telos to South African history) stunted her understanding of the present.